Fatty Acid and Amino Acid Profile of Mancadu Clam (Atrina vexillum) in Waai Village - Salamony, Meilita; Sohilait, Hanoch Julianus; Telussa, Ivonne (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Mancadu clam (Atrina Vexillum) is a food source for Maluku coastel communities with high nutritional value and contains various bioactive components, including fatty acids and amino acids. This study analyzed the content of fatty acids and amino acids in mancadu clams (Atrina Vexillum) in Waai village. Fatty acid analysis was carried out through a maceration extraction process with the Shaking Incubator method and transesterification using the microwave. Amino acid analysis was carried out by hydrolysis for 12 hours. The results of the research, the fatty acids of mancadu clams contain 7 fatty acid components, consisting of 2 saturated fatty acids, namely hexadecanoic or methyl palmitate, which is the most significant component (17.61%) and heptadecanoic acid (13.43%). Unsaturated fatty acids are hydrosinnamic acid (15.01%), 5,8,11,14- eicosatetranoic acid/omega-6 fatty acid (7.2%), octadecanoic acid (6.65%), 9-Octadecanoic acid (5.1%) and 8,11-eicosadinoic acid or FUPA (4.68%). The results of amino acid analysis of mancadu clams (Atrina Vexillum) on 18 amino acids obtained 6 types of essential amino acids namely leucine, valine, isoleucine, threonine, methionine and arginine which the largest compound from acid hydrolysis (1150.94 mg/Kg). There are 7 types of nonessential amino acids: glutamic acid, alanine, serine, glycine, aspartic acid, and proline.